A preliminary study of self-reported food selectivity in adolescents and young adults with autism spectrum disorder. (July 2015) - Kuschner, Emily S.; Eisenberg, Ian W.; Orionzi, Bako; Simmons, W. Kyle; Kenworthy, Lauren; Martin, Alex; Wallace, Gregory L.
Highlights: We examine self-reports of food selectivity in adolescents/adults with autism spectrum disorder. Adolescents/adults with autism spectrum disorder report preferring familiar foods. They also report disliking foods with particular textures and strong flavors. Lower daily living skills ratings correlate with self-reports of preferring familiar foods. Food selectivity is an important issue in adolescence/adulthood in autism spectrum disorder. Abstract: Although it is well-established that picky eating is a common feature of early development in autism spectrum disorder (ASD), far less is known about food selectivity during adolescence and adulthood. Using portions of the Adult/Adolescent Sensory Profile, food selectivity self-ratings were obtained from 65 high-functioning adolescents/young adults with ASD and compared to those of 59 typically developing controls matched on age, IQ, and sex ratio. Individuals with ASD reported preferring familiar foods (food neophobia) and disliking foods with particular textures and strong flavors. Providing linkage to everyday behavior, parent ratings of daily living skills were lower among individuals with ASD and food neophobia than among those without food neophobia. Food selectivity continues to be an important issue for adolescents/young adults with ASD.